PENGARUH PERBEDAANBENTUK BEBERAPA MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) - CATUR NUR WIBISONO; Teguh Supriyadi; Tyas SOEMARAH KURNIA DEWI (JURNAL ILMIAH AGRINECA, 2011)
This research aimed at knowing (1) the effect of kind of manure in growth and yield of peanut, (2) the effect of manure form in growth and yield of peanut, and (3) the effect of kind and form manure in growth and yield of peanut. The research was carried out at Slawi with the hight of location 40 metre from see level, the type of soil is latosol from 10th July  up to 30th October 2010. Design used was factorial with elementary pattern Completely Randomized Block Design consist of two treatment factor.  The first, kind of manure (K) consist of K1(bufallo manure), K2 (goat manure), and K3 (chicken manure). The Second, form of manure (B) consist of B1 (solid without extract), B2 (solid without extract), and B3 (rest of extract). There are 9 treatment combination i.e K1B1, K1B2, K1B3, K2B1, K2B2, K2B3, K3B1, K3B2, and K3B3. Result of the research showed that (1) kind of manure to take effect in fresh weight of plant, dry weight of plant, dry seed weight each one of plant, dry seed weight each one portion, and 100 dry seed weight. But, not effect in hight of plant, sum of pod each one of plant, sum green pod each one of plant, and Fill pod weight each of one plant, (2) The form of manure to take significant effect in sum of pod each one of plant, Fill pod weight each of plant, dry seed weight each one of plant, and 100 dry seed weight. But, not significant effect in hight of plant, fresh weight of plant, dry weight of plant, sum green pod each one of plant, and dry seed weight each one portion. (3) Kind manure and form of the menure to take effect significant to fresh weight of plant, dry weight of plant sum of pod each one of plant, Fill pod weight each of one plant, dry seed weight each one of plant, dry seed weight each one portion, and 100 dry seed weight. But, it’s not significant effect in hight of plant and sum green pod each one of plant. (4) Liquid chicken manure has the best effect in growth and yield of peanut.